2021
DOI: 10.1055/s-0041-1736319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Triple-Negative versus Luminal A Breast Cancer Subtype on Choice of Autologous versus Implant-Based Delayed-Immediate Breast Reconstruction

Abstract: Background Triple-negative (TN) and luminal A breast cancer molecular subtypes have divergent clinical and prognostic characteristics for breast cancer patients. Our study aims to compare the reconstructive choice of these two groups from the time they receive a tissue expander (TE) to the time they complete autologous or implant-based breast reconstruction. Methods A total of 255 patients who underwent delayed-immediate breast reconstruction with TE placement from 2013 to 2017 diagnosed with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…There have been several reports of increased fat necrosis in reconstructed breasts treated with radiotherapy [14][15][16][17][18] In this regard, immediate-delayed reconstruction has been recommeded as an option to avoid radiation therapy to the autologous reconstruction. [19][20][21] Alternatively, our study found that the volume ratio of the reconstructed breast had no decrease in the radiotherapy group, which was in accordance with other previous reports (p = 0.222, Supplementary Table 1). 22,23 This result may be due to the lower incidence of fat necrosis in our study population.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…There have been several reports of increased fat necrosis in reconstructed breasts treated with radiotherapy [14][15][16][17][18] In this regard, immediate-delayed reconstruction has been recommeded as an option to avoid radiation therapy to the autologous reconstruction. [19][20][21] Alternatively, our study found that the volume ratio of the reconstructed breast had no decrease in the radiotherapy group, which was in accordance with other previous reports (p = 0.222, Supplementary Table 1). 22,23 This result may be due to the lower incidence of fat necrosis in our study population.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…Given that a free flap is a major surgery that brings in healthy, nonradiated excess abdominal tissue, these results are not surprising and are in line with a previous study by Dickey et al, which shows that patients with a higher BMI and those undergoing radiation therapy are significantly more likely to elect for autologous reconstruction. 25 Patients who ultimately had autologous reconstruction had a TE in place for 48 days longer than patients who had exchange to an implant. This longer TE duration is likely the result of several factors including waiting for the patient to recover after completing radiation and surgeon availability when scheduling a free flap.…”
Section: Discussionmentioning
confidence: 99%
“…7 8 The reasons for this include (1) early reports of higher flap complication rates in immediate reconstruction followed by radiation, (2) limitations in treatment planning due to guidelines for postmastectomy radiation based on findings discovered at the time of mastectomy, and (3) potential for the flap to interfere with effective delivery of radiation to the chest wall. 9 10 11 12 22 23 24 25 26 The optimal timing of reconstruction after radiation remains an ongoing debate. Many believe that longer delays allow for recovery of acute inflammatory changes induced by radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although patient and treatment factors guide discussions and decisions for timing of reconstruction with anticipated radiation therapy (RT), delayed or delayed-immediate reconstruction remains the most common approach with anticipated radiation. 7 8 9 10 11 12 The prevailing assumption is that longer delays are needed to allow sufficient time for recovery of radiation treatment effects to tissues. This is supported by studies reporting higher complications rates when reconstruction is performed before 12 months.…”
mentioning
confidence: 99%